2008
DOI: 10.3844/ajptsp.2008.111.124
|View full text |Cite
|
Sign up to set email alerts
|

Hormetic and Non-Hormetic Dose-Response Functions in Stress Effects on Memory and Synaptic Plasticity: Issues and Mechanisms

Abstract: Over a century of behavioral research has shown that stress can exert both positive and negative effects on memory. We have explored the idea that the complex effects of stress on learning and memory can be characterized by hormetic-and non-hormetic dose-response functions, in which stress may either stimulate or impair brain memory mechanisms, depending, in part, on the timing and duration of the stress experience. Extensive work has shown that acute stress or corticosteroid administration has a biphasic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 155 publications
(190 reference statements)
2
2
0
Order By: Relevance
“…It was found that serotonin contributed a crucial role on both acquisition and consolidation processes (Kumar et al, 2007). However, numerous neurotransmitters had been proposed to contribute the important role on learning and memory including acetylcholine (Zoladz and Diamond, 2008;Bustamam et al, 2008). Our findings clearly demonstrated that the alcoholic extract of K. parviflora rhizome enhanced swimming time while decreased immobility time in forced swimming test in the same manner as Fluoxetine, a Serotonin Reuptake Inhibitor (SSRI) (Mohajeri et al, 2007).…”
Section: Discussionsupporting
confidence: 65%
“…It was found that serotonin contributed a crucial role on both acquisition and consolidation processes (Kumar et al, 2007). However, numerous neurotransmitters had been proposed to contribute the important role on learning and memory including acetylcholine (Zoladz and Diamond, 2008;Bustamam et al, 2008). Our findings clearly demonstrated that the alcoholic extract of K. parviflora rhizome enhanced swimming time while decreased immobility time in forced swimming test in the same manner as Fluoxetine, a Serotonin Reuptake Inhibitor (SSRI) (Mohajeri et al, 2007).…”
Section: Discussionsupporting
confidence: 65%
“…Because past research has suggested that emotional arousal augments or impairs learning, it may be the case that printed information concerning a crisis of this magnitude is alarming enough; presenting graphic and vivid images of the threatening and uncertain crisis, without complementing them with "cool" media accounts of the events, may lead to an excessive level of arousal that inhibits learning. This would be consistent with the curvilinear relationship between arousal and learning posited by numerous authors (see Zoladz & Diamond, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, there is evidence that people are inclined to remember general (or "gist") information after a moderately arousing event but will lose details when pushed to extreme levels of emotional arousal (Zoladz & Diamond, 2008). Because emotional arousal may augment or impair learning depending on the circumstances, past research has not clearly indicated how much people will learn from coverage of a crisis, especially if they are directly affected.…”
Section: Emotion Arousal and Mediated Learningmentioning
confidence: 99%
“…It's believed that the hormones released in response to stressful events act to better preserve the gist of experiences (McGaugh, 1992), whereas a number of mechanisms, such as restricted attentional focus at the time of events, serve to impair memory for details when events are highly arousing (Safer, Christianson, Autry, & Österlund, 1998). Because emotional arousal both preserves and impairs learning depending on the degree of arousal, nature of the material tested, and temporal relationships between the aroused state and learning (Zoladz & Diamond, 2008), it's unclear how much people will learn when exposed to educational information embedded in disaster coverage.…”
Section: Psychological Impact Of Crises and Crises Coveragementioning
confidence: 99%